Customer satisfaction and the adoption of Mtn momo for peer to peer transactions among university students - Kenneth Ongodia (My University, 2024)
This study examines the effect of the adoption of MTN momo pay for peer to peer transactions among university students focusing mainly on the impact of perceived usefulness, perceived ease of use and customer satisfaction. A mixed method approach was employed involving the collection of quantitative data through a structured questionnaire administered to a sample of 48 university students, nevertheless descriptive statistics such as means and standard deviations were used to analyze the data and assess the relationship between the key variables of the study. The study sought to answer three main research objectives namely; examining the effect of perceived usefulness on MoMo adoption, examining how perceived ease of use impacts customer satisfaction and the effect of the combined influence of both factors on overall customer satisfaction with the service.The results indicated that both perceived usefulness and perceived ease of use significantly influence the adoption and customer satisfaction levels among university students who use MTN MoMo Pay, however, perceived usefulness was found to be a major determinant in encouraging students to adopt and continue using the service for their financial transactions, while perceived ease of use contributed to their overall satisfaction with the service. In addition, a strong correlation was observed between customer satisfaction and continued use of MTN MoMo Pay.The findings suggest that to enhance customer satisfaction and adoption rates, MTN MoMo should focus on improving the functionality and user friendliness of its platform especially the momo app, while also emphasizing the perceived benefits of the service. The recommendations for further research and practical improvements are provided to ensure continued user engagement and satisfaction with MTN MoMo Pay among university students.